Analisis Kualitas dan Kuantitas Steganografi dengan Interpolasi pada Citra Medis - Meirista Wulandari; Indah Soesanti (Forum Teknik, 2015)
Nowadays sharing of medical images through Internet is very popular to make telediangosis, telesurgeries and teleconsultation. Steganography is an art of hiding information inside of a media, which is called cover media. This research presents steganography image on medical image. The medical image is divided into two areas edge and non-edge area. Each area has its embedding and extraction algorithm. A medical data in a text form is hidden insidemedical image by interpolation technique. Interpolation technique is used to increase the embedding capacity. After steganography process, medical data and its cover image and its earlier image must be recovered and reversibled from extraction its stego image. The results show an average of the optimum embedding capacity is 103,404 bit with average PSNR is 41.8682 dB. Furthermore, analysis on texture of the stego image is done by this research. The analysis shows the impact of embedding process. The results of texture analysis is embedding process gives a big impact to energy 27.9199%, entropy 5.4725% and skewness 1.5266%.Keywords: steganography, data, medical image, interpolation, texture image